Enhanced microwave absorption features of Ba3Co2Fe24O41 hexaferrite by high lanthanium doping concentration. Issue 6 (6th February 2022) - Tran, Ngo; Yang, Ruey‐Bin; Jeong, Woo Hyun; Manh, Do Hung; Phan, The‐Long; Lee, Bo Wha
Abstract: Controlling material structure and its electromagnetic properties, including complex permittivity and permeability, could enhance the microwave absorption performance of the material in terms of reflection loss and effective absorption bandwidth. In this study, La‐substituted barium hexaferrite, Ba3− x La x Co2 Fe24 O41 ( x = 0, 0.1, 0.3, and 0.5) compounds were successfully prepared using the solid‐state reaction method, and their corresponding microstructures, static magnetic properties, and electromagnetic features in 2–18 GHz were investigated. The doping of La content increased saturation magnetization, coercivity, and remnant magnetization. The Ba2.7 La0.3 Co2 Fe24 O41 epoxied sample with 3.5 mm thickness possessed an excellent microwave absorption of −47.3 dB at 3.52 GHz, and its corresponding effective absorption bandwidths were 3.75 GHz (2.25–6 GHz) and 0.57 GHz (17.43–18 GHz). It is shown that doping with various La concentrations on Ba3 Co2 Fe24 O41 can be used as an effective technique to tune the performance of microwave absorbers based on barium hexaferrite.